Tarascon pocket pharmacopoeia 2019 classic shirt-pocket edition - Hamilton, Richard J. (Jones & Bartlett Learning, 2019)
The Tarascon Pocket Pharmacopoeia® 2019 Classic Shirt-Pocket Edition details FDA approved drug dosing, available trade and generic formulations, metabolism, safety in pregnancy and lactation, relative drug pricing information, Canadian trade names, and an herbal & alternative therapies section.